2001
DOI: 10.1021/jp010255e
|View full text |Cite
|
Sign up to set email alerts
|

NMR and X-ray Spectroscopy of Sodium−Silicon Clathrates

Abstract: The 23Na and 29Si NMR spectra of the sodium−silicon clathrate materials Na8Si46 and Na x Si136 (1 < x < 24) and the parent Zintl phase NaSi have been studied in detail with a view to ironing out a number of ambiguities in the published literature and to determining properties of these potential thermoelectric materials. Sharp spectra are obtained only when the clathrate cages are close to fully occupied by Na, so that crystallographic symmetry is achieved. Signals from Na in the small and large cages of both s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
35
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 58 publications
10
35
0
2
Order By: Relevance
“…This oxide layer has been directly observed in the Na x Si 136 clathrates, 37 and can present difficulties in both densification 38 and interpretation of the measured transport properties. 39 The SPS technique has been shown to be very effective in the preparation and consolidation of a diverse range of materials.…”
Section: Resultsmentioning
confidence: 98%
“…This oxide layer has been directly observed in the Na x Si 136 clathrates, 37 and can present difficulties in both densification 38 and interpretation of the measured transport properties. 39 The SPS technique has been shown to be very effective in the preparation and consolidation of a diverse range of materials.…”
Section: Resultsmentioning
confidence: 98%
“…Powder samples of these clathrates were synthesized at the National Research Council of Canada as described elsewhere. 13,15 The occupation numbers of the guest atoms were determined by x-ray diffraction analysis via Rietveld refinement. Si 136 is a clathrate of type II and crystallizes in the space group Fd3m.…”
Section: ͑1͒mentioning
confidence: 99%
“…Moewes et al 11 found indications that sodium is almost fully ionized in Na 8 Si 46 , whereas Conesa et al 12 reported only a partial charge transfer of sodium valence electrons to the silicon framework which was obtained from theoretical calculations. An x-ray absorption study of the Si L edge in Na 8 Si 46 by He et al 13 demonstrated, via the shift of the core level binding energy, that there is a large charge transfer from sodium to the silicon framework. Moreover, band structure calculations emphasize that a rigid-band model is valid in case of Na 8 Si 46 , showing that the charge transfer in this system is substantial.…”
mentioning
confidence: 99%
“…Pour ce dernier, la raie du 23 Na dans les cages Si 20 se situe à w 1770 ppm, la raie du 87 Rb dans les cages Si 28 à w 3700 ppm et les raies du silicium à 275 ppm (Si(1) en 8a), 420 ppm (Si(2) en 32e) et 735 ppm (Si(3) en 96 g); les intensités correspondantes sont dans les rapports 1:3,9:12,1. He et al ont repris de manière détaillée l'interprétation des spectres de NaSi, Na 8 Si 46 et Na x Si 136 avec 0 x 24, qu'ils ont complétée par des études de spectroscopies XPS et XANES [164]. Pour NaSi, la raie de résonance du 23 Na est observée à 48,6 ppm et celle du 29 Si à e364 ppm, sous forme d'une raie large à deux composantes non résolues provenant de la présence de deux sortes de sites cristallographiques pour le silicium [6].…”
Section: Caractérisation Des Clathrates Par Résonance Magnétique Nuclunclassified
“…Une étude comparative des spectres de RMN MAS (magic angle spinning) du 23 Na dans les clathrates Na x Si 136 (x w 24) et Na 16 Cs 8 Si 136 a été effectuée par Pouchard [162] et Jaussaud [165], qui a confirmé l'interprétation de He et al [164]. Pour la phase Na x Si 136 , deux raies principales sont observées à 1800 e la plus intense e et 1600 ppm, ainsi que de nombreuses bandes de rotation de satellites quadripolaires de part et d'autre de la raie située à 1600 ppm, qui correspond par conséquent aux atomes de sodium situés dans les cages Si 20 les plus nombreuses mais les moins symétriques (Fig.…”
Section: Caractérisation Des Clathrates Par Résonance Magnétique Nuclunclassified